What kind of information do early parental report instruments provide on language ability at 3;6 when used at 2;0? A longitudinal comparison study - Surakka, Susanna; Vehkavuori, Suvi-Maria; Saaristo-Helin, Katri; Stolt, Suvi (Frontiers in Psychology, 2023)
Various parental report instruments are available for assessing children’s language skills at the end of the second year. However, comparison studies on their usability are lacking, and it is also open to question what kind of information the instruments provide when used in a parallel manner. This longitudinal study investigated which of the available three parental report instruments, when used at 2;0 (year;month), provides the most representative information on language development at 3;6. In addition, since most of the parental report instruments available focus specifically on expressive language, the role of receptive language ability was also investigated when analyzing the explanatory value of parental report instruments. The participants were 68 typically developing children. At 2;0, language skills were measured using the following measures: the Infant-Toddler Checklist of the Communication and Symbolic Behavior Scales Developmental Profile (ITC), the Short Form and Long Form versions of the Finnish Communicative Development Inventories (FinCDI-SF, FinCDI-LF), and the Reynell Developmental Language Scales III (RDLS). The outcome measures were receptive/expressive/general language ability at 3;6 measured using RDLS. The results of parental report instruments were significantly and positively associated with language ability at 3;6. The correlation between the combined value of ITC and FinCDI-SF and later language ability was stronger than correlations for each measure separately. The regression models with the results of parental report instruments as predictors explained 18%–22% (p < 0.00) of the variability in the total RDLS score. However, when receptive language ability at 2;0 was included in the models as a predictor, R2 increased considerably (46%–48%, p < 0.00). The results adduce the usability of parental report measures along with the importance of measuring receptive language skills at two years of age. In summary, this study provides important insights into the clinical evaluation of early language ability.